VLADIMIR DEMIYANOVICH SUKHODOLO – A SOLDIER, SCIENTIST, PERSON (THE 95TH ANNIVERSARY OF BIRTHDAY) - I. V. Sukhodolo; I. V. Milto (Бюллетень сибирской медицины, 2014)
The creative biography of famous domestic scientist, doctor of medical Sciences, Professor Vladimir Demianovich Sukhodolo (1919–2000) has been presented. The principal events of his scientific and social activities are reflected.